Fabrication and characterization of branched carbon nanostructures - Malik, Sharali; Nemoto, Yoshihiro; Guo, Hongxuan; Ariga, Katsuhiko; Hill, Jonathan P. (Beilstein Journal of Nanotechnology, 2016)
Carbon nanotubes (CNTs) have atomically smooth surfaces and tend not to form covalent bonds with composite matrix materials. Thus, it is the magnitude of the CNT/fiber interfacial strength that limits the amount of nanomechanical interlocking when using conventional CNTs to improve the structural behavior of composite materials through reinforcement. This arises from two well-known, long standing problems in this research field: (a) inhomogeneous dispersion of the filler, which can lead to aggregation and (b) insufficient reinforcement arising from bonding interactions between the filler and the matrix. These dispersion and reinforcement issues could be addressed by using branched multiwalled carbon nanotubes (b-MWCNTs) as it is known that branched fibers can greatly enhance interfacial bonding and dispersability. Therefore, the use of b-MWCNTs would lead to improved mechanical performance and, in the case of conductive composites, improved electrical performance if the CNT filler was better dispersed and connected. This will provide major benefits to the existing commercial application of CNT-reinforced composites in electrostatic discharge materials (ESD): There would be also potential usage for energy conversion, e.g., in supercapacitors, solar cells and Li-ion batteries. However, the limited availability of b-MWCNTs has, to date, restricted their use in such technological applications. Herein, we report an inexpensive and simple method to fabricate large amounts of branched-MWCNTs, which opens the door to a multitude of possible applications.
Keywords: branched multiwalled carbon nanotubes; carbon nanostructures; carbon nanotubes; graphene nanoribbons; multiwalled carbon nanotubes